1991
DOI: 10.1088/0264-9381/8/8/016
|View full text |Cite
|
Sign up to set email alerts
|

Principal null directions of the Curzon metric

Abstract: The Curzon metric has an invariantly defined surface, given by the vanishing of the cubic invariant of the Weyl tensor. On a spacelike slice, this surface has the topology of a 2-sphere, and surrounds the singularity of the metric. In Weyl coordinates, this surface is defined by R=m where R= square root ( rho 2+z2). The two points where the z-axis, the axis of symmetry, cuts this surface, z=m and -m, have the interesting property that, at both of them, the Riemann tensor vanishes. The Weyl tensor is of Petrov … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…The vanishing of the quantity between the brackets in (16) is just the Laplace equation ∇ 2 ν = 0 in cylindrical coordinates with an axis of symmetry about z. The field equation (16) gives the linear Newtonian gravity; then the field of two monopoles can be introduced as a superposition of the gravitational field of two singularities as…”
Section: Exact Teleparallel Two Body Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…The vanishing of the quantity between the brackets in (16) is just the Laplace equation ∇ 2 ν = 0 in cylindrical coordinates with an axis of symmetry about z. The field equation (16) gives the linear Newtonian gravity; then the field of two monopoles can be introduced as a superposition of the gravitational field of two singularities as…”
Section: Exact Teleparallel Two Body Problemmentioning
confidence: 99%
“…Also, the solution shows a peculiar singularity behaviour, whereas it exhibits a directional singularity allows the particles approaching the singularity along the axis of symmetry to be geodesically complete accessing to some new region of the space-time [14]. This leads some to conclude that the singularities in Curzon solution are actually rings rather point-like particles [15][16][17]. Interestingly, for the superposition of a ring and another body, a membrane-like singularity appears besides the strut one [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…The "ring" has finite radius but infinite circumference [10]. Rather remarkably late was the computation of w2R in [13], a work which gave visual information on the CC metric based on the principal null directions. This procedure gives much less information than the visualization procedure considered here.…”
Section: The Curzon-chazy Metricmentioning
confidence: 99%
“…Every light ray emitted from it becomes infinitely redshifted, so that it is effectively invisible [10]. Studying the principal null directions, it was found that this spacetime has an invariantly hypersurface ρ 2 + z 2 = M, on which the Weyl invariant J (determinant of the Weyl five complex scalar functions) vanishes [1,10]. Furthermore, this metric is Petrov type D, except at two points (z = ±M) that intersect the axis ρ = 0, where it is of Petrov type O [1].…”
Section: Introductionmentioning
confidence: 99%